Sistemas parabólicos : aplicações em fluidos com capilaridade trifásico - Toon, Eduard (Universidade Federal de São Carlos, 2009)
We study degenerate parabolic systems arised in three-phase capillary flows in porous media under a pressure control at the inflow and outflow boundaries. We perform a mathematical study of such systems for a class of linear capillarity pressure functions. To this end, a theory of nondegenerate parabolic approximations is developed. It has been proved the unique solvability of the initial boundary problems.
Keywords: Sistemas parabólicos; Capilaridade; CIENCIAS EXATAS E DA TERRA::MATEMATICA